The Effect of Ethanol Extract from Mangosteen Pericarps towards Parasitemia in Plasmodium berghei-Inoculated Mice - Debora R. Marito; Susy Tjahjani; Khie Khiong (Universitas Kristen Maranatha, 2016)
Mangosteen pericarps contains fenolic antioxidant, such as xanthone that acts as free radical scavenging substances and preventing heme polymerization. In this research we evaluated the effect of ethanolic extract of mangosteen pericarps on the parasitemia in Plasmodium berghei-inoculated mice and compared its antimalarial activity with artemisinin monotherapy in reducing the parasitemia in Plasmodium berghei-inoculated mice. Deutschland Denken Yoken (DDY) Â mice were randomly divided into 5 groups and inoculated by Plasmodium berghei and given 0.1 mL aquadest (KN), 0.1 mg of artemisinin (KP), 2.5 mg (E1), 0.5 mg (E2) and 0,1 mg (E3) of ethanolic extract from mangosteen pericarps in 0.1 mL aquadest in 3 days. The parasitemia was observed on one day before the treatment, namely on the first day and on the day after the last treatment. We found a highly significant decrease highly significant decrease of the parasitemia in each treatment group compared to the Negative Control group (p < 0.01), and the decrease of parasitemia level in E1 group is similar to the artemisinin monotherapy group (p < 0.05).Â Â Keywords: ethanol extract of mangosteen pericarps, artemisinin, Plasmodium berghei, malaria